2022
DOI: 10.3389/fnins.2022.860208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of artificial intelligence in neuroradiology with development of a novel workflow-efficient picture archiving and communication system-based automated brain tumor segmentation and radiomic feature extraction

Abstract: PurposePersonalized interpretation of medical images is critical for optimum patient care, but current tools available to physicians to perform quantitative analysis of patient’s medical images in real time are significantly limited. In this work, we describe a novel platform within PACS for volumetric analysis of images and thus development of large expert annotated datasets in parallel with radiologist performing the reading that are critically needed for development of clinically meaningful AI algorithms. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The mean Dice scores of 0.91 for TC and 0.88 for WT of cross-validation on the internal cohort were comparable to those reported for adult GBM segmentation using state-of-the-art deep learning models. 42,43 Although worse than the internal cohort, TC segmentation for the external cohort (mean Dice=0.74) is still comparable to the 0.62-0.74 Dice scores reported in a recent study of automatic segmentation of subregions of pediatric brain tumors 26 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The mean Dice scores of 0.91 for TC and 0.88 for WT of cross-validation on the internal cohort were comparable to those reported for adult GBM segmentation using state-of-the-art deep learning models. 42,43 Although worse than the internal cohort, TC segmentation for the external cohort (mean Dice=0.74) is still comparable to the 0.62-0.74 Dice scores reported in a recent study of automatic segmentation of subregions of pediatric brain tumors 26 .…”
Section: Discussionsupporting
confidence: 75%
“…The mean Dice scores of 0.91 for TC and 0.88 for WT obtained on the internal cohort were comparable to those reported for adult GBM segmentation using state-of-the-art deep learning models. 43,44 The results on the external cohort were similar for WT, an indication of model generalizability and robustness when applied to independent data with different imaging and patient characteristics. Although results were inferior for TC segmentation for the external cohort (mean Dice=0.74), they are comparable to the 0.62-0.74 Dice scores reported in a recent study of automatic segmentation of subregions of pediatric brain tumors 26 .…”
Section: Discussionmentioning
confidence: 66%
“… 38–40 For example, incorporation of segmentation algorithms and volumetric tools directly into the picture archiving and communication system (PACS) can facilitate clinical practice workflows. 41 Furthermore, PACS-based tools to automatically track lesion growth can make response assessment more reliable and efficient. 38 One study showed that interrater agreement for time to progression was significantly greater with an AI-based tool for tracking longitudinal tumor volume changes compared to manual 2D measurements using the RANO criteria.…”
Section: Moving Beyond Bidimensional Methods Of Response Assessmentmentioning
confidence: 99%
“…Finding the clinical uses of ML algorithms in clinical practice and identifying the areas of clinical care that can be enhanced by artificially generated algorithms are thus the next steps in neuro-oncology imaging [ 96 ].…”
Section: Prognosismentioning
confidence: 99%